ANALISIS RENCANA KERJA DAN ANGGARAN PERUSAHAAN (RKAP) TAHUN 2015 (Studi Kasus pada PT. ASDP Indonesia Ferry (Persero) Kantor Cabang Surabaya) - Putri, Eryna; Achmad, Komarudin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aimed to analyze the performance of 2014 as the basis for planning budget of revenues and expenses for 2015. This research used a descriptive method with case study approach. The data of the research were obtained through the collection, directly from the company. The result of the research indicate that the budget of revenues and expenses that the company arranged for 2015 is quite good, but still not perfect. Researchers recommend improvements drafting the work plan and budget to be equipped with performance indicators for each of the strategic plans, programs, and activities as well as completing work plan and budget up to prepare the proforma balance sheet. Â Keywords: Performance analysis, Work Plan and Budget, Strategic plans, Programs, and Activities.